Caspofungin-induced β(1,3)-glucan exposure in Candida albicans is driven by increased chitin levels - Andrew S. Wagner; Stephen W. Lumsdaine; Mikayla M. Mangrum; Todd B. Reynolds (mBio, 2023)
ABSTRACT To successfully induce disease, Candida albicans must effectively evade the host immune system. One mechanism used by C. albicans to achieve this is to mask immunogenic β(1,3)-glucan epitopes within its cell wall under an outer layer of mannosylated glycoproteins. Consequently, induction of β(1,3)-glucan exposure (unmasking) via genetic or chemical manipulation increases fungal recognition by host immune cells in vitro and attenuates disease during systemic infection in mice. Treatment with the echinocandin caspofungin is one of the most potent drivers of β(1,3)-glucan exposure. Several reports using murine infection models suggest a role for the immune system, and specifically host β(1,3)-glucan receptors, in mediating the efficacy of echinocandin treatment in vivo. However, the mechanism by which caspofungin-induced unmasking occurs is not well understood. In this report, we show that foci of unmasking co-localize with areas of increased chitin within the yeast cell wall in response to caspofungin, and that inhibition of chitin synthesis via nikkomycin Z attenuates caspofungin-induced β(1,3)-glucan exposure. Furthermore, we find that both the calcineurin and Mkc1 mitogen-activated protein kinase pathways work synergistically to regulate β(1,3)-glucan exposure and chitin synthesis in response to drug treatment. When either of these pathways are interrupted, it results in a bimodal population of cells containing either high or low chitin content. Importantly, increased unmasking correlates with increased chitin content within these cells. Microscopy further indicates that caspofungin-induced unmasking correlates with actively growing cells. Collectively, our work presents a model in which chitin synthesis induces unmasking within the cell wall in response to caspofungin in growing cells. IMPORTANCE Systemic candidiasis has reported mortality rates ranging from 20% to 40%. The echinocandins, including caspofungin, are first-line antifungals used to treat systemic candidiasis. However, studies in mice have shown that echinocandin efficacy relies on both its cidal impacts on Candida albicans, as well as a functional immune system to successfully clear invading fungi. In addition to direct C. albicans killing, caspofungin increases exposure (unmasking) of immunogenic β(1,3)-glucan moieties. To evade immune detection, β(1,3)-glucan is normally masked within the C. albicans cell wall. Consequently, unmasked β(1,3)-glucan renders these cells more visible to the host immune system and attenuates disease progression. Therefore, discovery of how caspofungin-induced unmasking occurs is needed to elucidate how the drug facilitates host immune system-mediated clearance in vivo. We report a strong and consistent correlation between chitin deposition and unmasking in response to caspofungin and propose a model in which altered chitin synthesis drives increased unmasking during drug exposure.